2014
DOI: 10.2147/jpr.s62492
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic pain lack somatic markers during decision-making

Abstract: Abstract:Patients with chronic pain have impaired cognitive functions, including decision making, as shown with the Iowa gambling task (IGT). The main aim of this study was to elucidate whether patients' decision making is associated with a lack of the anticipatory skin conductance response (SCR). An increase in anticipatory SCR before making unfavorable choices is known to guide decisions in healthy controls during the IGT. Since several brain regions involved in decision making are reported to have altered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…The results indicate that pain increases risk seeking for monetary gains but not for monetary losses. Although in line with previous research on chronic pain patients (Apkarian et al 2004 ; Berger et al 2014 ; Biagianti et al 2012 ; Elvemo et al 2014 ; Tamburin et al 2014 ; Verdejo-García et al 2009 ; Walteros et al 2011 ), these findings partly go against dual-process theories, which predict that inhibition of system 2 leads to greater reliance on automatic biases such as the reflection effect of prospect theory (Evans 2003 ; Evans and Stanovich 2013 ; Kahneman and Frederick 2002 ; Kirchler et al in press; Porcelli and Delgado 2009 ). Thus, our findings suggest that pain does more than inhibit the reflective system 2—it produces risk seeking behavior for potential rewards.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results indicate that pain increases risk seeking for monetary gains but not for monetary losses. Although in line with previous research on chronic pain patients (Apkarian et al 2004 ; Berger et al 2014 ; Biagianti et al 2012 ; Elvemo et al 2014 ; Tamburin et al 2014 ; Verdejo-García et al 2009 ; Walteros et al 2011 ), these findings partly go against dual-process theories, which predict that inhibition of system 2 leads to greater reliance on automatic biases such as the reflection effect of prospect theory (Evans 2003 ; Evans and Stanovich 2013 ; Kahneman and Frederick 2002 ; Kirchler et al in press; Porcelli and Delgado 2009 ). Thus, our findings suggest that pain does more than inhibit the reflective system 2—it produces risk seeking behavior for potential rewards.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with chronic pain keep choosing cards from both kinds of decks and therefore end up with less money than controls (Apkarian et al 2004 ; Biagianti et al 2012 ; Tamburin et al 2014 ; Verdejo-García et al 2009 ; Walteros et al 2011 ). This learning impairment seems to be due to a lack of somatic markers, because chronic pain patients’ physiological arousal does not increase when they pick cards from disadvantageous decks, whereas it does in healthy controls (Elvemo et al 2014 ). Patients with chronic pain are also more risk taking on tasks that do not involve a learning component, especially when high potential gains (as opposed to losses) are at stake (Berger et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using the famous Iowa gambling task of Bechara and colleagues, participants began to generate anticipatory SCRs whenever they pondered a disadvantageous (risky) choice, before they explicitly knew it was disadvantageous. A few studies that investigated other types of anticipatory responses, such as HR, revealed inconsistent results (e.g., Crone, Somsen, van Beek, & van der Molen, 2004; Crone & van der Molen, 2007; Elvemo, Nilsen, Landrø, Borchgrevink, & Håberg, 2014; Osumi & Ohira, 2009; Studer & Clark, 2011). Moreover, to our knowledge, no previous study has examined whether anticipatory autonomic responses also occur before the decision to conceal information.…”
mentioning
confidence: 99%
“…Patients with chronic pain have been found to have impaired performance in the IGT-that is, they keep choosing cards from both kinds of decks (Apkarian et al, 2004;Biagianti et al, 2012;Tamburin et al, 2014;Verdejo-García et al, 2009;Walteros et al, 2011; but see Mongini et al, 2005). The reduced performance has been suggested to be due to a lack of somatic markers, because patients' physiological arousal does not increase when they choose cards from the bad decks (Elvemo et al, 2014). However, it is unclear from these studies how pain influences risk preferences per se, because the IGT involves choosing between options with initially unknown values and probabilities (and thus involves a learning component rather than simple choices between outcomes with known values and probabilities) and also involves weighting immediate over longer-term outcomes.…”
Section: Decision Making In Chronic Pain Patientsmentioning
confidence: 99%